Adverse selection, learning, and competitive search - Karin Mayr-Dorn (Global Labor Organization (GLO), 2020)
I develop a dynamic version of the competitive search model with adverse selection in Guerrieri, Shimer and Wright (2010). My model allows for an analysis of the effects of firm learning on labor market efficiency in the presence of search frictions. I find that firm learning increases relative expected earnings in high-ability jobs and, thereby, enhances imitation incentives of low-ability workers. The net effect on the aggregate expected match surplus and unemployment is indeterminate a priori. Numerical results show that firm learning does not increase labor market efficiency.
Keywords: D82; D83; J64; 330; job search; on-the-job effort; asymmetric information; learning